Hepatitis B virus elimination status and strategies in circumpolar countries, 2020. Issue 1 (1st January 2021) - Haering, Celia; McMahon, Brian; Harris, Aaron; Weis, Nina; Lundberg Ederth, Josefine; Axelsson, Maria; Olafsson, Sigurdur; Osiowy, Carla; Tomas, Kristina; Bollerup, Signe; Liitsola, Kirsi; Archibald, Chris; et al.
ABSTRACT: Hepatitis B virus (HBV) infection remains a global health threat. The World Health Organization (WHO) established a goal to eliminate HBV infection as a public health threat by 2030, and defined targets for key interventions to achieve that goal. We evaluated HBV burden and relevant national recommendations for progress towards WHO targets in circumpolar countries. Viral hepatitis experts of circumpolar countries were surveyed regarding their country's burden of HBV, achievement of WHO targets and national public health authority recommendations for HBV prevention and control. Eight of nine circumpolar countries responded. All countries continue to see new HBV infections. Data about HBV prevalence and progress in reaching WHO 2030 elimination targets are lacking. No country was able to report data for all seven WHO target measures. All countries have recommendations targeting the prevention of mother-to-child transmission. Only the USA and Greenland recommend universal birth dose vaccination. Four countries have recommendations to screen persons at high risk for HBV. Existing recommendations largely address prevention; however, recommendations for universal birth dose vaccination have not been widely introduced. Opportunities remain for the development of trackable targets and national elimination planning to screen and treat for HBV to reduce incidence and mortality.